EVALUASI EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS DI BENGKEL ANUGRAH UTAMA MOTOR - suar08 suardani; I Made Pradana Adiputra; Anantawikrama Tungga Atmadja (Universitas Pendidikan Ganesha, 2026)
This study aims to evaluate the implementation of the Accounting Information System (AIS) in the cash receipts and cash disbursements processes at Bengkel Anugrah Utama Motor. The research employed a descriptive qualitative approach through in-depth interviews, direct observations, and document analysis of financial records during the period of October–November 2025. The findings indicate that financial transaction recording is still carried out semi-manually using cash books. The procedures for cash receipts and disbursements are not supported by adequate segregation of duties, thereby increasing the risk of recording errors and the potential for fraud. Furthermore, cash reconciliation is only performed at the end of the month, which leads to delays in detecting cash discrepancies. Limited technical skills among human resources also hinder the adoption of digital-based AIS. These conditions result in low financial information accuracy and slow managerial decision-making processes. The study recommends the implementation of an integrated computerized accounting system and capacity-building through training to enhance the effectiveness, accountability, and sustainability of cash management practices.